The 14-3-3 protein Bmh1 functions in the spindle position checkpoint by breaking Bfa1 asymmetry at yeast centrosomes - Caydasi, Ayse Koca; Miçooğullari, Yağmur; Kurtulmus, Bahtiyar; Palani, Saravanan; Pereira, Gislene (Molecular biology of the cell, 2014)
In addition to their well-known role in microtubule organization, centrosomes function as signaling platforms and regulate cell cycle events. An important example of such a function is the spindle position checkpoint (SPOC) of budding yeast. SPOC is a surveillance mechanism that ensures alignment of the mitotic spindle along the cell polarity axis. Upon spindle misalignment, phosphorylation of the SPOC component Bfa1 by Kin4 kinase engages the SPOC by changing the centrosome localization of Bfa1 from asymmetric (one centrosome) to symmetric (both centrosomes). Here we show that, unexpectedly, Kin4 alone is unable to break Bfa1 asymmetry at yeast centrosomes. Instead, phosphorylation of Bfa1 by Kin4 creates a docking site on Bfa1 for the 14-3-3 family protein Bmh1, which in turn weakens Bfa1-centrosome association and promotes symmetric Bfa1 localization. Consistently, BMH1-null cells are SPOC deficient. Our work thus identifies Bmh1 as a new SPOC component and refines the molecular mechanism that breaks Bfa1 centrosome asymmetry upon SPOC activation.